Impact of oral P2Y12 inhibitors on residual thrombus burden and reperfusion indexes in patients with ST-segment elevation myocardial infarction. Issue 9 (September 2016) - Di Vito, Luca; Versaci, Francesco; Limbruno, Ugo; Pawlowski, Tomasz; Gatto, Laura; Romagnoli, Enrico; Cattabiani, Maria Alberta; Micari, Antonio; Trivisonno, Antonio; Marco, Valeria; Prati, Francesco
Abstract : Aims: We sought to assess the impact of different oral P2Y12 receptor inhibitors on residual thrombus and reperfusion indexes in ST-segment elevation myocardial infarction patients enrolled in the COCTAIL II trial, which included 128 primary percutaneous coronary interventions randomized to intracoronary vs. intralesion abciximab bolus with or without thrombectomy. Methods: Patients were divided into three groups: clopidogrel ( n = 44), prasugrel ( n = 45) and ticagrelor ( n = 39). Residual intra-stent thrombus was quantified by optical coherence tomography using both the number of cross-sections with thrombus area more than 10% and thrombus volume. Reperfusion indexes included thrombolysis in myocardial infarction (TIMI) flow, corrected TIMI frame count, myocardial blush grade (MBG) and complete ST-segment resolution (≥70%). Results: In the prasugrel group, optical coherence tomography depicted a lower percentage of cross-sections with residual thrombus area more than 10% [4.0 (1.0–8.5)], as compared with clopidogrel [8.0 (1.0–15.0), P = 0.011] and ticagrelor [7.0 (3.0–13.5), P = 0.026].A higher thrombus volume was found in the clopidogrel group 4.0 mm 3 (2.7–6.2) as compared with the prasugrel group [2.8 mm 3 (1.8–4.4), P = 0.023], whereas the other between-group comparisons yield no significant differences. The frequency of MBG 3 was higher in the prasugrel group (73.3%) as compared with clopidogrel (45.5%) and ticagrelor [(56.4%), P = 0.027]. Final TIMI flow, TIMI frame count and ST resolution were not significantly different across the three groups ( P = 0.423, 0.179 and 0.848, respectively). At multivariate analysis, pretreatment with prasugrel was independently associated with MBG 3 (odds ratio = 3.93; 95% confidence interval = 1.01–15.39). Conclusion: Prasugrel loading dose was associated with a lower percentage of cross-sections with residual thrombus area more than 10% as compared with both clopidogrel and ticagrelor, although intrastent thrombus volume was not significantly different between prasugrel and ticagrelor. The frequency of MBG 3 was the only reperfusion index that was significantly more prevalent in prasugrel treated group as compared with clopidogrel and ticagrelor groups.